Efficient Optimization of High‐Quality Epitaxial Lithium Niobate Thin Films by Chemical Beam Vapor Deposition: Impact of Cationic Stoichiometry - Anna L. Pellegrino; Estelle Wagner; Francesca Lo Presti; William Maudez; Simon Kolb; Rashmi Rani; Antoine Bernard; Stephan Guy; Alban Gassenq; Marina Raevskaia; Christian Grillet; Rahma Moalla; et al. (Advanced Materials Interfaces, 2023)
Abstract Lithium niobate is a material of special interest for its challenging functional properties, which can suit various applications. However, high quality 200‐mm LixNb1‐xO3 thin film grown on sapphire substrate have never been reported so far which limits these potential applications. This paper reports the efficient optimization of high quality LiNbO3 thin film deposition on sapphire (001) substrate through chemical beam vapor deposition in a combinatorial configuration. With this technique, flow ratio of Li/Nb can be tuned from ≈0.25 to ≈2.45 on a single wafer. Various complementary characterizations (by means of diffraction, microscopy and spectroscopy techniques) have been performed at different areas of the film (different cationic ratios) in order to investigate the impact of the cationic stoichiometry deviation on the film properties. Close to cationic stoichiometry (LiNbO3), the epitaxial films are of high quality (single phase in spite of two in‐plane domains, low mosaicity of 0.04°, low surface roughness, refractive index and band gap close to bulk values). Deviating from the stoichiometry conditions, secondary phases are detected (LiNb3O8 for Nb‐rich flow ratios, and Li3NbO4 with partial amorphization for Li‐rich flow ratios). LiNbO3 films are of high interest for various key applications in data communications among others.